ДИСФУНКЦИЯ ПЕЧЕНИ У КАРДИОХИРУРГИЧЕСКИХ БОЛЬНЫХ В РАННЕМ ПОСЛЕОПЕРАЦИОННОМ ПЕРИОДЕ - О. В. Соколова; В. П. Тюрин (Архивъ внутренней медицины, 2014)
We investigate the frequency and reasons of liver dysfunction in the early postoperative period at patients after heart surgery. The liver dysfunction occurred at 120 from 663 (18%) operated patients in the early postoperative period. We revealed a distinct connection between a type of a surgery performed and liver dysfunction, which more frequently followed multivalve procedures and combined operative treatment like valve reconstruction and myocardial revascularization. Amongst causes, which contribute liver dysfunction we sorted 5 main ones: prolonged hypoxia in preoperative term, trauma due to surgery and intraoperative hypoxia, toxic medications, reactivation of a viral hepatitis, sepsis. A term, when liver dysfunction advances, depends on these causes.